Integrated Effect of Fertilizers on Soil pH, EC and Organic Matter Content - AL-Makhlof, Hassin; Mohammed, Hassan; Ahmed, Gomoa; Emhammed, Muftah (Journal of Pure & Applied Sciences, 2022)
Two field experiments in split-plot design were carried out in the winter season of  2014-2015 at Mansoura University Farm, Egypt, to investigate the effect of biochar, compost, and chicken manure with different rates of mineral fertilization on soil pH, EC, and organic matter content. Treatments of organic were biochar, compost, and chicken manure, while the studied mineral fertilizer treatments (NPK) took with rates of 50,75,100, and 125 %. The obtained results can be summarized in; biochar, addition led to an increase in the pH of wheat (Sakha 68) soil by 8.73 %, compost, and chicken manure decreased the pH of wheat soil by 8.30 and 8.19% compared with 0.0 organic addition, where the same amendment with the same order increased pH of barley (Gemmiza 123) soil by 8.65, and reduce with 8.30 and 8.18% of compost and chicken manure. Biochar, compost, and chicken manure treatments increased values of  EC 2 , 2.43, and 2.10 dS m-1 of wheat soil and 2.80, 2.23, and 2.14 dS m-1 of barley, respectively. Organic matter improved and the highest result was found with chicken manure 2.798 and 2.767 % of wheat and barley soil. Mineral fertilizer decreased both pH of wheat and barley soil as well as increased EC and organic matter up to the highest level used. A significant organic fertilizer type - mineral fertilization dose interaction was found with the most of tested treatments. The highest effect on pH in soil paste was found in the interactions between biochar with mineral treatments compared to other treatments of both wheat and barley soil. The best mean value of EC was recoded with the interaction between compost and 100 % NPK treatment (2.76 dS m-1) of wheat soil, a similar trend was also achieved with barley soil (3.29 dS m-1). Chicken manure -125 % of recommended NPK treatment gave the heights values of wheat and barley organic matter content, 2.798 and 2.767 %.  Respectively.